THE PERCEPTION OF ELECTRICAL ENGINEERING TRADE TEACHERS ON THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGY FOR TEACHING IN TECHNICAL COLLEGES IN ADAMAWA AND GOMBE STATES OF NIGERIA - Duhu, P.C.; Mbaga, E.V.; D.W, Quahha; Danzaria, L. (European Scientific Journal, ESJ, 2014)
This study was conducted to determine the perception of electrical engineering trade teachers on the role of information and communication technology (ICT) for classroom instructions in Technical Colleges in Adamawa and Gombe States of Nigeria. A forty item structured Questionnaire was distributed to twenty-six electrical engineering trade teachers from Adamawa and Gombe States technical colleges for collection of data. The questionnaire was face validated and trial tested on five electrical engineering trade teachers from Taraba state. Test- re-test method of establishing reliability was used and cronbanch Alpha formula was used to calculate a reliability index of 0.78. Mean and standard deviation were used to answer the research questions. Student’s t-test was used to test the three hypotheses formulated to guide the study. The study revealed that electrical engineering trade teachers lack some basic ICT skills like skills in database and spreadsheet. The findings revealed among others the following: electrical engineering teachers perceived themselves as having inadequate skills required to use the ICT for classroom instructions. It also revealed that teachers were not comfortable with regards to the role of ICT vis-à-vis their in classroom management/control and loyalty from students. Recommendations based on the findings included among others that electrical engineering trade teachers should be given sufficient retraining on how to use ICT for teaching and learning processes. Teachers should acquire the requisites knowledge and skills for integrating the ICT into education for instructional delivery.